2017
DOI: 10.21010/ajtcam.v14i3.26
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Chemical Composition and Antimicrobial Activities of Bioactive Molecules From Date Palm (Phoenix Dactylifera L.) Pollens and Seeds

Abstract: Background: Natural resources have been the crucial origin of chemical elements. They have been used in many traditions as alternative medicines. The chemical profiling of some plant extracts and essential oils related to different plants were followed to unveil their most active components. In this paper, Phoenix dactilyfera L was selected as a host plant to investigate the composition of different organs with different cultivars. Materials and method:The antibacterial and antifungal activities of the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…Interestingly, flavonoids of some medicinal plants have been used for centuries against some human diseases, they revealed different mode of actions against bacterial cells, such as inhibit DNA synthesis and cytoplasmic membrane function [15]. In agreement to our assumption, Bentrad et al [16] have evaluated the antibacterial activity of the pollens (from flowers) of P. dactylifera, the organic fraction that was rich in flavonoids exhibited high antibacterial activity. Moreover, the methanol extract of pollen was reported to contain six types of phenolic compounds that showed active antibacterial effects [17].…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, flavonoids of some medicinal plants have been used for centuries against some human diseases, they revealed different mode of actions against bacterial cells, such as inhibit DNA synthesis and cytoplasmic membrane function [15]. In agreement to our assumption, Bentrad et al [16] have evaluated the antibacterial activity of the pollens (from flowers) of P. dactylifera, the organic fraction that was rich in flavonoids exhibited high antibacterial activity. Moreover, the methanol extract of pollen was reported to contain six types of phenolic compounds that showed active antibacterial effects [17].…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, cytohistological techniques have already revealed them in seeds teguments of some other date cultivars such as Deglet Nour and Takerbucht [ 24 ]. We have shown that anthocyanidins from date seeds inhibit the proliferation of some endophyte fungi from five special fungi from Fusarium oxysporum spice [ 15 ], which causes significant economic damage to cultivated plants and the environment.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work [ 15 ], the determination of the quantitative content of flavonic aglycones was carried out. The TLC of organic extracts (ether phase) provided a good separation of the molecules and an acceptable visibility of the spots under UV (wood light).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than antimicrobial activities such as antibacterial, antifungal, and antimalarial bioactivities, plant extracts from the Middle East are known to have anti-cancer and anti-tumor properties, with the added ability to also enhance the immune system and induce apoptosis among carcinoma cells; this will enable the possibility of curing cancers and tumors, without much dependence on chemotherapy agents [49]. The anti-cancer and anti-tumor activities in the plant extract are due to the presence of various groups of compounds, such as alkaloids, diterpenes, diterpenoquinone, purine-based compounds, lactonic sesquiterpene, proteins, and macrolides [106].…”
Section: Anti-cancer and Anti-tumor Activitymentioning
confidence: 99%